Disputa territorial a direito à moradia: o caso da ocupação Vista Alegre do Juá em Santarém, Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
The understanding of the territory is extremely necessary for the social understanding of those involved, as this concept makes it possible to understand the socio-spatial relations of the territory covered. The expansion of the public debate in relation to the case of the Vista Alegre do Juá occupation, located on the banks of Avenida Fernando Guilhon, in the city of Santarém, was the impetus for this work, as it houses the outline of this debate in a local scale the objective of this research is to understand how the urban land dispute occurs in the context of an occupation, and specifically to characterize the process of spontaneous occupations in Brazil in the 20th century, to identify regionalization regarding spontaneous occupations and territorial dispute and finally to analyze as occurs the territorial dispute in the middle of the right to housing in the case of Vista Alegre do Juá. The method adopted for the production of this work was the qualitative, exploratory research and case study. Therefore, there are some conflicts that have been generated since the beginning of the occupation of Vista Alegre do Juá, influenced by the logic of capital involved. Currently, the conflict of interest occurs between the population occupying this disputed area, in which the largest portion are poor people, and the companies Buriti Empreendimentos e Construções LTDA and Shopping Rio Tapajós Shopping, both undertakings claim that this occupation harms them in their business . Finally, given what was exposed in the work, it can be said that one of the causes for unplanned urban growth, that is, land occupations, territorial disputes (land disputes), are the development policies carried out in the region, that is. for decades it has been generating an urban expansion.
Keywords: Disputa; Território; Ocupação; Regionalização; Moradia; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS